Kesadaran Hukum Masyarakat Menghadapi Sengketa Hukum dan HAM di Nagari Barung Barung Belantai - Henni Muchtar; Yusnanik Bachtiar; Akmal Akmal; Zaky Farid Luthfi; Fatmariza Fatmariza (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
The objectives of the Community Services (PKM) in Nagari Barung Barung Belantai, Koto XI Tarusan District, Pesisir Selatan Regency are: (1) to increase knowledge of legal and human rights to the community and the Nagari government especially land issues and other civil cases. (2) to improve the quality of the skills of the community and the Nagari government to understand the flow of reporters/complaints and the operational resolution of cases of violations of human rights law in accordance with applicable procedures, and (3) to improve the capabilities and skills of the community and the Nagari government how to complain and where they complain the violations of human right. The method used is counselling, consultation, and case resolution according to the conditions faced and equipped with a reflective communicative method. The results achieved were that 85% of the participants had the knowledge, skills and attitudes towards legal and human rights settlements, especially in resolving cases of communal, tribal, and communal land and other legal cases.